Contamination with per- and polyfluoroalkyl compounds (PFAS) in natural waters and drinking water - Kryłów, Małgorzata (Instal, 2022)
EU 2020/2184 Directive of December 16, 2020 on the quality of water intended for drinking introduces limits on concentrations of organic substances, which are not included in the current Ordinance of the Minister of Health (item 2294 of December 7, 2017) on the quality of water intended for drinking. The new substances included in the Directive are per- and polyfluoroalkyl compounds (PFAS). These compounds are highly toxic, immuno suppressive and widespread in the natural environment. The paper presents an overview of the current knowledge on the PFAS content in surface and ground waters. Perfluoro-octanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) have been included in Annex B of the Stockholm Convention, which has resulted in a restriction of their production and use. Short-chain PFASs such as perfluorobutanoic acid (PFBA) and perfluorobutanesulfonic acid (PFBS) have begun to be used in industrial products. A similar change was noticed in the profile of PFAS detected in the aquatic environment. The article presents also a brief review of these compounds removal effectiveness in water treatment processes for drinking waters.
Keywords: PFAS; PFOS; PFOA; surface waters; drinking water